"Any idea how fast 'It's just a mask!' can turn into 'It's just a vaccine!'": From mask mandates to vaccine mandates during the COVID-19 pandemic. Issue 51 (5th December 2022) - Martin, Sam; Vanderslott, Samantha
Highlights: This paper provides an overview of the key trends and themes of discussion concerning attitudes to and the adoption of two health measures to control COVID-19 in the UK and US. Using social media data collected via Twitter, we explore how different public groups react when confronted with mandatory policies. We find two constituencies have been brought together: pre-existing vaccine critical 'anti-vaccine' groups and newly formed oppositional COVID-19 groups. The oppositional COVID-19 constituencies vary in composition and nature, but the central focus is a disagreement about the seriousness and threat of COVID-19 and public health measures to control COVID-19. What unites many disparate interests is an aversion to mandates. Abstract: Protests starting in the summer of 2020, notedly in the US and UK, have brought together two constituencies: pre-existing anti-vaccine groups and newly formed oppositional COVID-19 groups. The oppositional COVID-19 groups vary in composition and nature, but the central focus is a disagreement about the seriousness and threat of COVID-19 and with the public health measures to control COVID-19. What unites many disparate interests is an aversion to mandates. The compulsion to undertake particular public health activities such as mask-wearing and vaccination is a complex topic of public attitudes and beliefs alongside public health goals and messaging. We aim to analyse social media discussions about facemask wearing and the adoption of potential vaccines for COVID-19. Using media monitoring software Meltwater TM, we analyse English-language tweets for one year from 1st June 2020 until 1st June 2021. We pay particular attention to connections in conversations between key topics of concern regarding masks and vaccines across social media networks. We track where ideas and activist behaviours towards both health interventions have originated, have similarities, and how they have changed over time. Our aim is to provide an overview of the key trends and themes of discussion concerning attitudes to and adoption of health measures in the control of COVID-19 and how publics react when confronted with mandatory policies. We draw on an already extensive literature about mandatory vaccination policies to inform our assessment, from psychology and behavioural science to ethics, political theory, sociology, and public policy.